Seismic prediction technology for thin sandstone reservoir of Dainan Formation in Majiazui Oilfield - CHEN Hongcai, LI Zhaorui (Youqicang pingjia yu kaifa)
Dainan Formation in Majiazui Oilfield is characterized by developed fractures and is primarily composed of structural-lithologic reservoirs. The reservoirs exhibit thin vertical thickness and rapid lateral distribution changes, demanding high precision in reservoir prediction, which conventional seismic inversion methods struggle to meet. To address this challenge, the waveform indication simulation method was employed for thin reservoir prediction in the study area. This method, guided by waveform coherency, uses changes in seismic waveforms laterally instead of variogram functions to simulate target parameters, yielding high-precision inversion results that better conform to sedimentary and geological laws. Taking advantage of the dense and numerous development wells in the study area, and integrating geological, seismic, and well logging data, the spontaneous potential curve, which is sensitive to the reservoir, was selected for waveform indication simulation. This approach was used to predict the distribution of the main oil-bearing sand groups. The inversion results were analyzed in conjunction with the computation wells, check wells, and cross-fault wells, indicating that the waveform indication simulation has high vertical and lateral resolution. It can finely reflect the spatial variation of the reservoir. The main oil-bearing sand group's planar distribution was extracted and found to be consistent with the sedimentary patterns of the study area. Combined with the oil layer distribution map, the target oil-bearing sand group's distribution was re-evaluated, suggesting potential for rolling extension to the west beneath the Ma3 fault. This insight could guide further exploration and development strategies in the Majiazui Oilfield.